Optimization of protein content in earthworm-based fish feed formulation for catfish (Clarius gariepinus) - Zarina Zakaria; Noor Hasyierah Mohd Salleh; Alina Rahayu Mohamed; Ahmad Anas, N.G; Siti Nur Amirah Idris (Universiti Kebangsaan Malaysia, 2012)
The optimization of protein content in earthworm-based fish feed formulation was investigated in the study. Full factorial design (FFD) and central composite design (CCD) were used as a statistical tool to screen the range of the selected parameters and to optimize the process, respectively. Three components were combined in the fish feed formulation namely earthworm powder, chicken guts and soybean waste as the protein source. The optimum nutritional values were obtained at 25%, 25% and 5.95% for earthworm powder, soybean waste and chicken guts, respectively, to give an optimum protein content of 35.97%. Formulation of fish feed from earthworm powder can be an alternative in aquaculture industry in the near future.